2023
DOI: 10.1001/jamaneurol.2023.3206
|View full text |Cite
|
Sign up to set email alerts
|

Automated Large Vessel Occlusion Detection Software and Thrombectomy Treatment Times

Juan Carlos Martinez-Gutierrez,
Youngran Kim,
Sergio Salazar-Marioni
et al.

Abstract: ImportanceThe benefit of endovascular stroke therapy (EVT) in large vessel occlusion (LVO) ischemic stroke is highly time dependent. Process improvements to accelerate in-hospital workflows are critical.ObjectiveTo determine whether automated computed tomography (CT) angiogram interpretation coupled with secure group messaging can improve in-hospital EVT workflows.Design, Setting, and ParticipantsThis cluster randomized stepped-wedge clinical trial took place from January 1, 2021, through February 27, 2022, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Clinically relevant reductions in endovascular stroke therapy (EVT) in LVOs were recorded in a cluster randomized stepped-wedge clinical trial in Houston, Texas that assessed the primary outcomes of patients needing acute stroke triaging [ 51 ]. This study was conducted in four comprehensive stroke centers with 243 participants via enabling AI-automated CT angiogram coupled with secure messaging.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically relevant reductions in endovascular stroke therapy (EVT) in LVOs were recorded in a cluster randomized stepped-wedge clinical trial in Houston, Texas that assessed the primary outcomes of patients needing acute stroke triaging [ 51 ]. This study was conducted in four comprehensive stroke centers with 243 participants via enabling AI-automated CT angiogram coupled with secure messaging.…”
Section: Reviewmentioning
confidence: 99%
“…This study was conducted in four comprehensive stroke centers with 243 participants via enabling AI-automated CT angiogram coupled with secure messaging. This system resulted in a 9.8-minute reduction (96% CI, -16.9 to -2.6) in time from CT scan and initiation of EVT, further reducing the length of hospital stay and ultimately causing an 18% decrease in mortality [ 51 ]. With those previous numbers in mind, a 9.8-minute reduction is equivalent to 18.62 million neurons, 135.24 billion synapses, and 117.6 miles of axonal fibers potentially spared, per patient, due to the integration of AI and closed-loop messaging systems.…”
Section: Reviewmentioning
confidence: 99%
“…10 Minuten. Allerdings sind echte NeuroradiologInnen derzeit noch etwas genauerund leider langsamer [9,10]. Auch wenn diese konkreten KI-Anwendungen bereits Marktreife erlangt haben und zugelassen sind, gibt es zahlreiche weitere Proof-of-Concept-Studien zur Diagnosevorhersage und Entscheidungsunterstützung, deren prospektive Validierung und Nutzenbewertung noch aussteht [11,12,13].…”
Section: Einsatz Von Künstlicher Intelligenz In Der Notaufnahmeunclassified
“…As providers consider AI adoption, it is especially instructive to be aware of the different CAD types and their advantages and limitations across different diseases. In the case of CADt, several studies have indeed shown the potential for faster turnaround times and improved outcomes for prioritized exams 15 , 16 . However, the FDA has also recently released a letter “reminding health care providers about the intended use of radiological computer-aided triage and notification (CADt) devices for intracranial large vessel occlusion (LVO)”, including statements that such devices are not diagnostic and cannot rule out the presence of an LVO 17 , 18 .…”
mentioning
confidence: 99%